2015
DOI: 10.1107/s2053230x15007359
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic analysis of a nonstructural protein 15 mutant fromHuman coronavirus 229E

Abstract: Nonstructural protein 15 (nsp15), also called endoribonuclease, is a gene product of open reading frame 1b (ORF 1b) in coronaviruses. It is an important enzyme in the transcription/replication process involved in discontinuous negative-strand RNA synthesis. In this work, mutants of nsp15 from Human coronavirus 229E (HCoV-229E) were made based on structural analysis of the homologous nsp15s in Severe acute respiratory syndrome coronavirus (SARSCoV) and Mouse hepatitis virus (MHV). The I26A/N52A mutant of nsp15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Besides the test compounds, two references were included, i.e. K22 [( Z )- N -[3-[4-(4-bromophenyl)-4-hydroxypiperidin-1-yl]-3-oxo-1-phenylprop-1-en-2-yl]benzamide; 16 from ChemDiv] and GS-441524 (the nucleoside form of remdesivir; from Carbosynth). After five days incubation at 35°C, microscopy was performed to score virus-induced CPE.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the test compounds, two references were included, i.e. K22 [( Z )- N -[3-[4-(4-bromophenyl)-4-hydroxypiperidin-1-yl]-3-oxo-1-phenylprop-1-en-2-yl]benzamide; 16 from ChemDiv] and GS-441524 (the nucleoside form of remdesivir; from Carbosynth). After five days incubation at 35°C, microscopy was performed to score virus-induced CPE.…”
Section: Methodsmentioning
confidence: 99%
“…The first two structures of Nsp15 were determined from mouse hepatitis virus (MHV; Protein Data Bank [PDB] ids 2GTH, 2GTI 13 ) and SARS coronavirus (PDB id 2H85 14 ). Currently, there are in total eight structures available for Nsp15, including additional two from SARS-CoV (PDB ids 2OZK, 2RHB 15 ), one from MERS-CoV (PDB id 5YVD 16 ) and two from H-CoV-229E (PDB ids 4S1T, 4RS4 17 ). Among Nsp11 endoribonucleases, there are two structures determined for PRRSV homolog (PDB ids 5EYI, 5DA1 18 ), and two for equine arteritis virus (EAV, PDB ids 5HC1, 5HBZ 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, nsp15 was found to be active as a hexamer. This finding was confirmed for the nsp15s in several coronaviruses, including those of MHV, SARS-CoV, HCoV-229E, and turkey coronavirus nsp15 (25,27,33,34). Furthermore, the basic biofunctional unit of SARS-CoV nsp15 was confirmed to be a hexamer (33).…”
mentioning
confidence: 52%
“…In PDCoV nsp15, we found it was a mixture of monomers and dimers, and in several Alpha-, Beta-, and Gammacoronavirus nsp15s, the proteins have been identified as hexamers (25, 27, 33,34). Furthermore, according to the molecular clock analysis, the times to which these four coronaviruses could be traced were ϳ2400 BCE, 2800 BCE, 3300 BCE, 3000 BCE, corresponding to Alphacoronavirus, Gammacoronavirus, Betacoronavirus, and Deltacoronavirus, respectively (4).…”
Section: Evolution Of Nidovirus Endoribonucleasementioning
confidence: 86%